Formulation of Subject-Related Relationships: An Intervention Study on the Effect of Linguistic Scaffolds on Verbalization of Causal Structures in Geography Lessons - Heuzeroth, Johannes; Budke, Alexandra (Journal of Geography Education, 2021)
This paper examines the effectiveness of linguistic scaffolds on the development of students' geographical causal structures in the context of thinking in complex human-environment systems. For this purpose, content-related and linguistic characteristics of geographical causal structures were determined, and the effectiveness of scaffolds was statistically tested by means of an analysis matrix using a quasi-experimental, quantitative panel design. The results show that linguistic scaffolds improve the coherence of the content and thus the accuracy of geographical causal structures but have hardly any influence on the number of elements used and the relations developed. The results could constitute a starting point for the further development of linguistic scaffolds to make a valuable contribution to the development of systemic thinking skills.
Keywords: scaffolding, geographical causal structures, problem-solving, systemic thinking, intervention study